Cao dao, hò, vè miền Trung - Trương, Đình Quang; Nguyễn, Quang Nhân; Dương, Thái Nhơn; Nguyễn, Viết Trung (Văn hóa dân tộc, 2012)
Giới thiệu ca dao, hò, vè của đất Quảng Nam, Bình Định, Phú Yên, Ninh Hòa.